Direct coating of multifunctional zinc oxide-reduced graphene oxide interlayer on cathode for lithium-sulfur batteries. (20th June 2021) - Lo, Yi-Hsuan; Kuo, Ping-Lin; Wu, Jih-Jen
Highlights: A multifunctional ZnO NP-rGO NS interlayer was directly coated on S- rGO cathode. rGO network connecting interlayer and cathode offers an apt conductive pathway. Zn NPs perform as a polysulfide immobilizer to suppress the shuttle effect. Zn NPs also act as an electrochemical catalyst to accelerate the redox kinetics. This lightweight ZnO-rGO interlayer can buffer the volume expansion in the cathode. Abstract: In this work, a multifunctional interlayer composed of ZnO nanoparticles (NPs)-reduced graphene oxide (rGO) composite nanosheets was directly coated on the top of sulfur-rGO composite (S-rGO) cathode for the improvement of the electrochemical performances of lithium-sulfur batteries. With this configuration, the rGO network well connecting the interlayer and cathode provides an appropriate electrically conductive pathway for the discharge and charge processes. The soluble lithium polysulfides formed during the discharge process are efficiently absorbed on ZnO NPs to suppress the shuttle effect. In addition, the ZnO NP plays the role of an electrochemical catalyst to accelerate the redox kinetics. With the ZnO-rGO interlayer, the cathode also exhibits the considerably enhanced Li ion transfer/transport properties. The reversible conversion of sulfur to Li2 S2 /Li2 S therefore occurs in the ZnO-rGO interlayer to efficiently reutilize the retained active materials. Moreover, the ZnO-rGO interlayer, which accounts for ~8.5 wt% of the whole cathode, can buffer the volume expansion in the cathode to prevent irreversible structural destruction. Accordingly, a capacity degradation of 0.04% per cycle at 1C after 500 cycles with a capacity retention of 838 mAhg −1 is delivered by S-rGO cathode with the ZnO-rGO interlayer. Graphical abstract: Image, graphical abstract